Α-Glucosidase inhibitory activity and in vivo antihyperglycemic effect of secondary metabolites from the leaf infusion of Ocimum campechianum mill. (28th October 2019) - Ruiz-Vargas, Javier A.; Morales-Ferra, Dulce L.; Ramírez-Ávila, Guillermo; Zamilpa, Alejandro; Negrete-León, Elizabeth; Acevedo-Fernández, Juan José; Peña-Rodríguez, Luis M.
Abstract: Ethnopharmacological relevance: Wild basil ( Ocimum campechianum Mill.), an aromatic herb of the Lamiaceae family known as "albahaca de monte" (Spanish) or "x'kakaltun" (Mayan) in Yucatan, is used in Mayan traditional medicine to treat diabetes, as well as to alleviate fever symtoms, stomach pain, conjunctivitis, and various skin affections. Aim of the study: To isolate and identify the bioactive metabolites responsible for the α-glucosidase inhibitory activity previously detected in the leaf infusion O. campechianum . Materials and methods: The bioassay-guided fractionation and purification of the lyophilized infusion was carried out using a liquid-liquid partition procedure, followed by successive chromatographic purifications of the semipurified fractions. The isolated metabolites were identified by comparing their spectroscopic data with those reported in the literature. The liophylized infusion, together with the semipurified fractions, and the pure metabolites were tested for their antioxidant and α-glucosidase inhibitory activities, as well as their antihyperglycemic effect. Results: Chromatographic purification of the semipurified fractions led to the isolation of the polymethoxylated flavones 5-demethyl nobiletin (1 ) and 5-demethyl sinensetin (2 ), together with luteolin (3 ), methyl rosmarinate (4 ) and rosmarinic acid (5 ). Metabolites 4 and 5 appear to be responsible for the α-glucosidase inhibitory activity and the antihyperglycemic effect detected in the lyophilized infusion. A Lineweaver-Burk double reciprocal plot confirmed that the higher α-glucosidase inhibitory activity of 4 is of non-competitive nature. Both 4 and 5 caused a decrease in blood glucose higher than that caused by acarbose, a result that appears to be related to their strong α-glucosidase inhibitory activity. Even though flavonoids 1 –3 did not show a good inhibition of α-glucosidase, these products decreased blood glucose in the in vivo model, suggesting a different antihyperglycemic mechanism. Conclusions: The results confirm both the traditional use of O. campechianum and the importance of the leaf infusion as a potential source of antihyperglycemic agents. The isolation of 5-demethyl nobiletin (1 ) and 5-demethyl sinensetin (2 ) from O. campechianum and other Ocimum spp. suggests that polymethoxyflavones can be considered chemotaxonomical markers for the genus. Graphical abstract: Image 1